1987
DOI: 10.1038/hdy.1987.6
|View full text |Cite
|
Sign up to set email alerts
|

Copy-number dependent transpositions and excisions of the mdg-1 mobile element in inbred lines of Drosophila melanogaster

Abstract: The chromosomal location of the mobile element mdg-1 was studied in 17 highly-inbred lines of Drosophila melanogaster. Although some lines were stable for their pattern of insertion sites from the 15th to the 27th and 35th brother-sister generations, others showed a high rate of gain of new insertion sites or a high rate of excision (loss of elements). In one line, 8 new insertion sites on the third chromosome were associated with an inversion on this chromosome; there is evidence that the rearrangement occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 33 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The effective population size of D. melanogaster has been estimated to be between 10 6 (Kreitman 1983) and 10 5 (Schug et al 1998). The retrotransposition/transposition rates of TEs vary greatly across families in D. melanogaster, ranging from 0 to 3.94 3 10 À3 per element per generation (Ising and Block 1981;Biemont and Aouar 1987;Biemont et al 1990;Harada et al 1990;Nuzhdin andMackay 1994, 1995;Suh et al 1995;Maside et al 2000Maside et al , 2001. (Rates estimated from previous studies are summarized in Supplemental Table S1.)…”
Section: Forward Simulations Of the Population Genetics Of Pirts And mentioning
confidence: 99%
“…The effective population size of D. melanogaster has been estimated to be between 10 6 (Kreitman 1983) and 10 5 (Schug et al 1998). The retrotransposition/transposition rates of TEs vary greatly across families in D. melanogaster, ranging from 0 to 3.94 3 10 À3 per element per generation (Ising and Block 1981;Biemont and Aouar 1987;Biemont et al 1990;Harada et al 1990;Nuzhdin andMackay 1994, 1995;Suh et al 1995;Maside et al 2000Maside et al , 2001. (Rates estimated from previous studies are summarized in Supplemental Table S1.)…”
Section: Forward Simulations Of the Population Genetics Of Pirts And mentioning
confidence: 99%
“…We also observed hobo insertion in division 42B on the 2R arm; the four elements mdg-1, I, copia and P in the study of and many other sequences (297, 412, mdg-3, roo) hybridize to this chromosomal region (Potter et al, 1979;Strobel, Dunsmuir & Rubin, 1979;Pierce & Lucchesi, 1981;Ananiev et al, 1984;Belyaeva, Ananiev & Gvozdev, 1984;Bi6mont & Aouar, 1987;Leigh-Brown & Moss, 1987;Montgomery, Charlesworth & Langley, 1987;Bi6mont & Gautier, 1989). It is thus likely that some regions of the genome have particular chromosomal environments (DNA sequence, local chromatin structure) that are more suitable for the insertion of different elements (Bi6mont, 1992).…”
Section: Discussionmentioning
confidence: 72%
“…For natural populations, polymorphism both for presence of element type among strains and chromosomal location within strains has been observed for several TE families, including particularly copia-like elements (Potter et aL, 1979;Strobel et aL, 1979;Rubin, 1983;Montgomery & Langley, 1983;LeighBrown & Moss, 1987;Birmont & Gautier, 1988), mdg (Belyaeva et al, 1984;Birmont & Aouar, 1987), FB (foldback) (Bingham & Zachar, 1989), P (Ronserray & Anxolabrhbre, 1987;Boussy et aL, 1988;Engels, 1989) hobo (Blackman & Gelbart, 1989;Prriquet et al, 1989;Daniels et al, 1990;Pascual &Prriquet, 1991) andI (Bi6mont, 1986;Leigh-Brown & Moss, 1987;Ronsseray & Anxolabrhbre, 1987;Finnegan, 1989, also see article by C. Birmont, this volume). In laboratory crosses,/, P, and hobo have been found to actively promote hybrid dysgenesis (Brrgliano & Kidwell, 1983;Bucheton et al, 1984;Streck et al, 1986;Yannopoulos, Stamatis et al, 1987;Lim, 1988;Engels, 1989;Finnegan, 1989; see also articles by A.…”
Section: Introductionmentioning
confidence: 99%
“…Bucheton et al, this volume). While activity of an individual TE type in a cross has been shown to depend on the genetic structure and number of elements and on cytotype (Simmons, 1986;Stamatis et al, 1986;Birmont & Aouar, 1987;Boussy et al, 1988;Monastirioti et al, 1988;Yannopoulos et al, 1986;Jackson et al, 1988), there appears to be no clear pattern of synergistic interaction between elements of different families, either in terms of their chromosomal occupation sites or transpositional activity (Biemont et al, 1988;Eggleston et al, 1988;Charlesworth & Langley, 1989;Stamatis et al, 1989), although there has been at least one reported case where dysgenesis for one TE has been associated with the transposition of a second element type (Lewis & Brookfield, 1987). Although these effects have also been assumed to occur in natural populations of Drosophila melanogaster, direct observation of hybrid dysgenesis has so far been restricted to laboratory crosses, with the exception that apparent bursts of mutations observed in some wild populations have been attributed to dysgenesis-induced transposition (Berg, 1974).…”
Section: Introductionmentioning
confidence: 99%